INTEGRATING CORRECTIVE METHODS INTO TEACHERS’ PEDAGOGICAL PRACTICE - Yuldasheva Maftuna Mamurjon qizi (International Scientific and Current Research Conferences, 2025)
The integration of corrective methods into contemporary pedagogical practice represents a critical vector for enhancing educational efficacy and fostering adaptive learning environments. This article examines the theoretical foundations and practical implications of incorporating corrective strategies within teacher professional activities, emphasizing their role in addressing diverse learner needs and optimizing instructional outcomes. By synthesizing insights from cognitive psychology, educational diagnostics, and instructional design, the study elucidates how corrective interventions can be systemically embedded into lesson planning, assessment procedures, and classroom management techniques. Furthermore, the analysis explores the symbiotic relationship between teacher competence in corrective methods and the holistic development of students’ cognitive, emotional, and social skills. Empirical evidence from international educational research underscores the transformative potential of corrective integration, highlighting its capacity to mitigate learning gaps, enhance metacognitive awareness, and promote reflective teaching practices.